Impact of acute stress exposure on genome-wide DNA methylation - Melissa Miller; Ciara McAfee; Robin D. Brown; Shelby Sears; Cole Krautkramer; Rhea Gogia; Dennis Wylie; Robert A. Josephs; Frances A. Champagne (Scientific Reports)
Abstract DNA methylation (DNAm) is a stable epigenetic modification, yet plasticity in DNAm is associated with exposure to a broad range of experiences. Evidence from animal studies suggests that acute stress can induce DNAm changes in adulthood. However, there has been limited exploration of plasticity in the human epigenome in response to acute stress. In the current study we examine whether acute stress-induced shifts in DNAm occur in male (N = 27) and female (N = 28 female) participants who undergo a lab-based stress-induction protocol. Results from our within-subjects design indicate that acute stress induces both hypermethylation and hypomethylation in salivary DNA, including CpG sites within the GATA3, NINL, BACH2, PHACTR1 and KRTAP19-3 genes. Sex-specific effects of acute stress were found within the COL4A1 gene, with females exhibiting an increase, and males exhibiting a decrease in DNAm following acute stress. Further, we found that psychological stress reactivity (but not cortisol reactivity) predicted post-stress DNAm, and cortisol reactivity (but not psychological stress reactivity) predicted epigenetic aging. Taken together, these novel findings (a) support the hypothesis that DNAm can shift in response to an acute stressor, and (b) highlight the importance of understanding the unique pathways through which hormonal versus psychological responses to stress influence the epigenome.